FOREIGN SUPPORT CENTERS FOR RUSSIAN PRISONERS OF WAR IN 1914-1917 - Elick Evgenievich Abdrashitov (Наука. Инновации. Технологии)
This article is devoted to the activity of foreign support centers, organized by Russians and citizens of other states for fundraiser for compatriots, who were in prison camps in Germany and Austro-Hungary in 1914-1917.